Drought projection from CMIP6 Climate models over Morocco in the 21st century using the Standardized Precipitation Evapotranspiration Index (SPEI) - Moutia Sara; Sinan Mohamed (E3S Web of Conferences, 2024)
Quantifying how climate change drives drought in the 21st century is a priority to inform policy and adaptation planning in Morocco. SPEI drought index calculated from precipitation and temperature at 12 months’ time-scale covering the agricultural year September-August was carried out for each of the five models over the future period 2023-2099. The average changes across Morocco were obtained by comparing between the averages of SPEI values and the drought zone percentages (Light, Moderate, Severe and Extreme). Also, by comparing drought characteristics for the different 11-year time horizons 2023-2033, 2034-2044, 2045-2055, 2056-2066, 2067-2077, 2078-2088 and at the end 2089-2099. The study of future drought projections based on the SSP2-4.5 scenario of the CMIP6 models indicates a worsening of drought in Morocco during the second half of the century. Moderate drought is expected to predominate, with a sharp increase in the area affected by drought, even reaching 90% over six years. These results are essential for decision-makers in water resources management, highlighting the need to put in place strategies to mitigate the adverse effects of drought, including the efficient use of water resources.